The Origins of Severe Acute Respiratory Syndrome-Coronavirus-2 - Dwyer, Dominic E. (Seminars in Respiratory and Critical Care Medicine, 2023)
An outbreak of severe pneumonia of unknown cause was identified in Wuhan, China in December 2019: the causative agent was a novel betacoronavirus, severe acute respiratory syndrome-cotonavirus-2 (SARS-CoV-2), a virus that joins a list of coronaviruses causing severe (e.g., SARS and Middle East respiratory syndrome) or milder (e.g., 229E, OC43, NL63, and HKU1) respiratory tract infection. The World Health Organization (WHO) classified the spreading outbreak as a pandemic on March 11, 2020. Many SARS-related coronaviruses (SARSr-CoVs) have been identified in bats, particularly in Rhinolophus horseshoe bats, animals that are common in southern China and Southeast Asia. Many of the features of SARS-CoV-2 that facilitate human infection—the furin cleavage site, the receptor binding domain that binds to the human ACE2 receptor—can be identified in SARSr-CoVs. Related coronaviruses can be detected in pangolins and other animals, and human SARS-CoV-2 itself can infect various animals, some of which can transmit SARS-CoV-2 back to humans. Investigation by the WHO and others pointed to the initial outbreak being centered on the Huanan wet market in Wuhan where wild and farmed animals were sold, and where environmental testing revealed widespread SARS-CoV-2 contamination. This supports the hypothesis that bats, probably via an intermediate animal, are the origin of SARS-CoV-2. Other possible origins have been postulated, such as an accidental or deliberate laboratory leak, or virus present in frozen foods, but evidence for these ideas has not surfaced. Study of the origins of SARS-CoV-2 have been complicated by intense media and political commentary, features that may slow the studies required to understand the viral origins. Such studies are complex and may be slow: international openness and co-operation is vital. Origins explanations are needed to predict or prevent future pandemics and support the “One Health” approach to disease.
Keywords: SARS-CoV-2; origins; animals; World Health Organization